Hubungan Membaca Teks Bahasa Arab dengan Hasil Belajar Siswa Kelas VIII Pondok Pesantren Darul Hasanah Polewali Mandar - Latifah Mahmud; Nurming Saleh; Arief Fiddienika (Universitas Islam Ahmad Dahlan Sinjai, 2024)
This research is quantitative correlational research with the aim of finding out the relationship between the ability to read and understand Arabic texts and the learning outcomes of Class VIII students at the Darul Hasanah Polewali Mandar Modern Islamic Boarding School. The method in this research is a correlative descriptive method to describe and measure the degree of relationship between two variables, namely, the ability to read, understand Arabic texts (X) and the results of learning Arabic (Y). The objects of this research were class VIII students at the Darul Hasanah Polewali Mandar Modern Islamic Boarding School. The results of this research show that there is a relationship between the ability to read and understand Arabic texts and the learning outcomes of Class VIII students at the Darul Hasanah Polewali Mandar Modern Islamic Boarding School. The correlation value contained in this study was 0.4132 or in the range 0.40-0.599. This shows that the level of correlation/relationship between the ability to read and understand Arabic texts and the learning outcomes of Class VIII students at the Darul Hasanah Polewali Mandar Modern Islamic Boarding School is in the medium category.